CORRELATION OF CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) AND TOTAL ASSET TURNOVER (TATO) TO RETURN ON ASSETS (ROA) AT PT CISADANE SAWIT RAYA TBK PERIOD 2019-2023 - Harahap Adrie Fachrezi; Maidalena (RADJA PUBLIKA, 2025)
This study aims to investigate how Return on Assets (ROA) of PT Cisadane Sawit Raya Tbk is affected by Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) during 2019–2023. Quantitative method with associative approach is used. The relationship between variables is evaluated through multiple linear regression analysis. According to the partial test results (t-test), CR, DER, and TATO have a positive and significant impact on ROA, indicating that liquidity management, capital structure, and asset utilization efficiency play an important role in increasing the company's profitability. The simultaneous test results (F-test) show that CR, DER, and TATO simultaneously significantly affect ROA, showing that the combination of the three variables has a strong contribution to the company's profitability. From the perspective of agency theory, these results reflect that management has acted in accordance with the interests of the owners by optimizing the management of assets, capital, and debt to increase financial performance.